2020
DOI: 10.3390/nu12103166
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Non-Alcoholic Fatty Liver Disease: Nutritional Origins and Potential Molecular Mechanisms

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the number one chronic liver disease worldwide and is estimated to affect nearly 40% of obese youth and up to 10% of the general pediatric population without any obvious signs or symptoms. Although the early stages of NAFLD are reversible with diet and lifestyle modifications, detecting such stages is hindered by a lack of non-invasive methods of risk assessment and diagnosis. This absence of non-invasive means of diagnosis is directly related to the scarcity of lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 202 publications
1
31
0
1
Order By: Relevance
“…In another NHP model of maternal high-fat diet/obesity, baboon fetuses showed downregulation of Wnt-associated miR-199a-5p and miR-182-5p, a pattern associated with fibrogenesis (57,58). Together, these results suggest that in utero exposure to maternal WSD is temporally and spatially associated with an increase in activation of profibrotic pathways in the fetus and may explain earlier-onset severe disease noted in some children with NASH (4,9). WSD-exposed fetuses showed an increase in classic markers of oxidative stress in the liver, including increases in TBARS content, 4-HNE labeling, and JNK activation (20,22,59).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In another NHP model of maternal high-fat diet/obesity, baboon fetuses showed downregulation of Wnt-associated miR-199a-5p and miR-182-5p, a pattern associated with fibrogenesis (57,58). Together, these results suggest that in utero exposure to maternal WSD is temporally and spatially associated with an increase in activation of profibrotic pathways in the fetus and may explain earlier-onset severe disease noted in some children with NASH (4,9). WSD-exposed fetuses showed an increase in classic markers of oxidative stress in the liver, including increases in TBARS content, 4-HNE labeling, and JNK activation (20,22,59).…”
Section: Discussionmentioning
confidence: 78%
“…Obesity rates continue to increase and have reached epidemic proportions around the globe (1). Currently, nearly 50% of women who are pregnant in the US are overweight or obese (2)(3)(4). Accompanying maternal obesity is an increase in noncommunicable metabolic disorders in children, leading to a body of literature that suggests that metabolic disorders, including obesity, type 2 diabetes mellitus, cardiovascular disease, and nonalcoholic fatty liver disease (NAFLD), are often of intrauterine origin (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The similarity of liver and blood mtDNA mutations suggests that they can be inherited from the mother, not developed de novo. This assumption is supported by many cases of NAFLD development in early childhood when paediatric NAFLD was found to be associated not only with nutrition but also with MetS, T2DM, and the obesity of mothers [ 26 ]. In addition to the mtDNA mutations, inherited nuclear mutations may also be the primary cause of OS and higher mtDNA variability.…”
Section: Considering Nafld/nash As a Mitochondrial Diseasementioning
confidence: 96%
“…It has been closely associated with metabolic syndrome, and its incidence is growing rapidly [ 1 , 2 , 3 , 4 ]. Furthermore, the presence of NAFLD has been reported in obese children and adolescents [ 5 ], that are certainly at higher risk of cardiovascular diseases and metabolic complications in adult age [ 6 ]. Epidemiologic studies have demonstrated that the excessive consumption of free sugars in childhood is associated with NAFLD in overweight adults [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%